A framework for effective knowledge translation and performance delivery of Sport Scientists in professional sport. Issue 11 (2nd November 2021) - Bartlett, Jonathan D.; Drust, Barry
Abstract: Sport Science is considered the study and application of scientific principles and techniques to improve sporting performance. Thus, a key role of the Sport Scientist is to translate complex information into usable and contextual performance solutions for a range of different stakeholders. These stakeholders consist of athletes, coaches, recruiting, performance support, medical, administration and operations staff and have varying interests and priorities meaning the information required can be vastly different. In addition to these different needs, sport is fast-moving, diverse and complex meaning there are a number of potential translational barriers. Sport Science training programmes entail the development of technical knowledge and practical skills; however, little is considered in view of interpersonal craft skill development and knowledge translation (KT). Given the reported barriers and challenges to effective KT in sport, this lack of specific training may render KT as ineffective and suboptimal. Accordingly, in this article, we propose a framework and work-based training model with the aim of developing the KT process and performance delivery of Sport Scientists operating in professional sport. Firstly, we define the current perspectives and challenges for Sport Scientists in the context of KT, before proposing a framework that focusses on Evidence-Based-Practice, Philosophy, Recipients and Facilitation, in which Sport Scientists can use to develop their interpersonal craft and subsequent KT approach. We finish by presenting a model of sport science practitioner training; the professional sport-doctoral training programme, that combined with the framework, can be effective in developing Sport Scientists.